2018
DOI: 10.1021/acssuschemeng.8b01546
|View full text |Cite
|
Sign up to set email alerts
|

Rh-Catalyzed Hydrogenation of Amino Acids to Biobased Amino Alcohols: Tackling Challenging Substrates and Application to Protein Hydrolysates

Abstract: While protein-rich biomass waste is nowadays mainly used for animal feed, conversion of its amino acid constituents to nitrogenous chemicals is a potential higher value route. To that end, the hydrogenation of amino acids to amino alcohols was studied in this work. Using a bimetallic Rh-MoOx/SiO2 catalyst, glutamic acid was for the first time hydrogenated to the aminodiol in high yield. By minimizing partial reduction and consecutive hydrogenolysis, and by suppressing the competitive cyclization to pyroglutami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 78 publications
(176 reference statements)
0
30
0
Order By: Relevance
“…Moreover, the aromatic moieties in phenylalanine and tyrosine were completely reduced to their saturated analogs, but this side reaction has been observed for Ru‐based catalysts as well . Poisoning of the Rh catalyst by cysteine and methionine was avoided by applying an oxidative pretreatment with performic acid, to convert the S‐containing thiol and thioether groups into inert sulfonic acid and sulfone groups, which do not possess lone pairs anymore …”
Section: Amino Acids As Direct Precursors To Value‐added Chemicalsmentioning
confidence: 99%
“…Moreover, the aromatic moieties in phenylalanine and tyrosine were completely reduced to their saturated analogs, but this side reaction has been observed for Ru‐based catalysts as well . Poisoning of the Rh catalyst by cysteine and methionine was avoided by applying an oxidative pretreatment with performic acid, to convert the S‐containing thiol and thioether groups into inert sulfonic acid and sulfone groups, which do not possess lone pairs anymore …”
Section: Amino Acids As Direct Precursors To Value‐added Chemicalsmentioning
confidence: 99%
“…Transition metal-mediated hydrogenation 1,2 using Fe, 3 Co, 4 Ni, 5 Pd, 6,7 Pt, 8 Rh, 9,10 Ir, 11 Ru 12 or Mo 13 is a well-established procedure in research and industrial applications. However, this approach usually requires high hydrogen pressure, resulting in over reduction or functional group intolerance of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that Pt/TiO 2 promotes the reductive deamination of glutamic acid derivatives to form organic acids at 225°C for 24 h [54]. By the same research group of [54], decarbonylation of amino acids was attempted by Ru-based catalyst [55]. Reductive (hydrogenation) decarbonylation of valine to isobutylamine was developed in the presence of Ru-catalyst with isobutylamine yield of 87% in hydrothermal water at 150°C for 2 h.…”
Section: Previous Studies On Solid Catalytic Reaction Of Amino Acid Imentioning
confidence: 99%